Analysis of Predictive Ability of Earnings and Cash Flow on Future Cash Flows: Listed Banking in Indonesia Stock Exchange During Period 2009 – 2021 - Trisnadi, Asih Widhi; Etty Puji Lestari; Diki (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
The company's ability to generate cash in the future is the key for stakeholders to build expectations for the company. Therefore, the choice of variables used in modeling to predict future cash flows is the key to the precision of predictive modeling. The Financial Accounting Standard Board's recommendation states that accrual-based information regarding company value is a better basis for assessing company's historical and future performance than current year cash flow information. However, research regarding predictors of future cash flows suggests otherwise. This is due to the potential for asymmetric information from financial reports that are prepared as a financialshenanigans. In this research, the ability of net profit will be tested again to predict aggregate cash flow. The choice of aggregate cash flow rather than operating cash flow as in previous research is because net profit is generated not only from operating activities but also investment activities and financing activities.